2020
DOI: 10.1007/s11274-020-2806-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of site-specific dechlorinating microbial inocula capable of complete dechlorination enriched in anaerobic microcosms amended with clay mineral

Abstract: Short-chain halogenated aliphatic hydrocarbons (e.g. perchloroethene, trichloroethene) are among the most toxic environmental pollutants. Perchloroethene and trichloroethene can be dechlorinated to non-toxic ethene through reductive dechlorination by Dehalococcoides sp. Bioaugmentation, applying cultures containing organohalide-respiring microorganisms, is a possible technique to remediate sites contaminated with chlorinated ethenes. Application of site specific inocula is an efficient alternative solution. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…The same progress was observed for Dehalococcoides, although, in this case, a weaker increase was reported. Similar trends of microbial communities were found either natural [27,71] or modified by the addition of carbon substrates [54,64]. In such complex microbial communities, many competitions can be found that are partially discussed above.…”
Section: Molecular Biological Analysessupporting
confidence: 66%
“…The same progress was observed for Dehalococcoides, although, in this case, a weaker increase was reported. Similar trends of microbial communities were found either natural [27,71] or modified by the addition of carbon substrates [54,64]. In such complex microbial communities, many competitions can be found that are partially discussed above.…”
Section: Molecular Biological Analysessupporting
confidence: 66%
“…Other than the well-known and highly abundant organohalide-respiring D. mccartyi, additional genera identified in the SG sample A0 have been implicated in dechlorinating processes. Amongst them, the Euryarchaeota, genus Methanosarcina is a PCE and TCE dehalogenator [22,23] while the genus Methanosphaerula has been recently described as a member of an anaerobic dechlorinating enrichment [75]. Species belonging to genus Geomonas (Geobacter) are often present in environments tainted with chlorinated ethenes and play a pivotal role in anaerobically dechlorination of PCE to cis-DCE [12,21,55], as does Sulfurospirillum [20].…”
Section: Microbial Compositionmentioning
confidence: 99%